In vitro antioxidant and anti-inflammatory properties of Limonium algarvense flowers' infusions and decoctions: A comparison with green tea (Camellia sinensis) - Rodrigues, Maria Joao (2017)
This work reports the in vitro antioxidant and anti-inflammatory activities and toxicity of infusions and decoctions of Limonium algarvense flowers, and green tea. The total contents in different phenolic groups and the quantification of individual phenolics by HPLC are also reported. L. algarvense and green tea had similar antioxidant properties, except for hydroxyl radical-scavenging activity, higher on green tea, and iron chelating potential, higher on L. algarvense. The later species also had the uppermost anti-inflammatory potential. Green tea decoction had the highest content of phenolic groups, but the infusion of L. algarvense had higher amounts of salicylic, gallic and coumaric acids. L. algarvense was not toxic, whereas green tea was toxic for S17 cells. Under our experimental conditions, infusions and decoctions of L. algarvense flowers had similar or higher antioxidant and anti-inflammatory properties than green tea, and thus, may be useful for alleviating symptoms associated with oxidative and inflammatory-related diseases. (C) 2016 Elsevier Ltd. All rights reserved.